Railway transport as a tool for socio-economic development of the Russian regions (evidence from the Republic of Sakha (Yakutia)) - L. V. Khudyakova (Вестник Научно-исследовательского института железнодорожного транспорта)
The article is devoted to the identification of the influence effects of transport infrastructure in the social sphere and in the regional economic development. The Republic of Sakha (Yakutia) was selected to be an object for investigation. The general approach and the hypothesis of the study is that the transport infrastructure can be considered as a factor of well-being, which in turn brings economic and non-economic benefits to the region and is an important determinant of social and economic growth, and improvements to the level and quality of life. Thereby, transport as a part of economic system has the property of a powerful tool for social development capable to secure as follows: growth of regional product; exchange of commodities, and therefore efficient production specialization; the spread of advanced technologies; lower prices and better products; higher gains for producers and consumers; national wealth growth; direct or indirect increases in the level of industrial and commercial activity in all areas of practice; promotion of new territories development, involvement of new resources into the asset turnover; other gains in the socio-economic sphere lead to higher level and quality of life, mobility of population, expansion of social relations.